PELATIHAN DAN PEMBUATAN PAPER SOAP ORGANIK SEBAGAI AlLTERNATIF UMKM KREATIF PADA MASYARAKAT DIMASA PANDEMI COVID-19 - Wahyu Ramadhan; Siti Juariah; Wahyu Margi Sidoretno; Dewi Sartika Siagian; Fenny Anita (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
During the Covid-19 pandemic, many ways have been done to keep the environment and oneself in a clean, hygienic and healthy state. Many people use products that are made to behave in a healthy life in preventing various types of diseases as an effort to behave in a healthy life while remaining disciplined in carrying out health care procedures. One of the prokes is to wash your hands with soap. Keeping hands clean by using soap is a necessity to prevent exposure to viruses and bacteria. The method used in this service is practice or experimentation to increase public understanding. The purpose of this activity is to provide knowledge to the community in Kubang Jaya Village, Kec. Siak Hulu District. Kampar in making practical organic paper hand soap. This hand soap product can also encourage creativity and interest in trying to become an alternative to MSMEs for the community to become a profitable home-based business opportunity. To achieve this goal, the Abdurrab University community service team has provided training and applied how to produce Organic Paper Hand Soap. The resulting impact shows maximum results, the community is enthusiastic and understands how product manufacturing works, as well as successfully making products well.